2015
DOI: 10.4014/jmb.1506.06065
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo Controlled-Trial of a Probiotic Strain Lactobacillus sakei Probio-65 for the Prevention of Canine Atopic Dermatitis

Abstract: Canine atopic dermatitis (CAD) is a ubiquitous, chronic inflammatory skin disorder prevalent in dogs, which results in production of abnormal levels of IgE antibodies in reciprocation to an allergen challenge. In this study, administration of the probiotic strain Lactobacillus sakei probio-65 for 2 months significantly reduced the disease severity index in experimental dogs diagnosed with CAD. In addition, one month pre-medication of L. sakei probio-65 revealed significant difference in the PVAS score in exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 13 publications
(13 reference statements)
1
37
0
Order By: Relevance
“…Apart from the VAS, there are severity scales to grade skin lesions in clinical trials, such as CADESI-04 [18]. However, these scales are more useful in long term studies [10]. This is because the pruritus will decrease upon initial treatment, which is followed by improvement skin lesions over time, as the latter commonly are the result of scratching.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the VAS, there are severity scales to grade skin lesions in clinical trials, such as CADESI-04 [18]. However, these scales are more useful in long term studies [10]. This is because the pruritus will decrease upon initial treatment, which is followed by improvement skin lesions over time, as the latter commonly are the result of scratching.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pVAS scores of both groups decreased gradually throughout the investigation but were not significantly different from the baseline scores. These results were similar to previous studies that have demonstrated the efficacy of oral administration of Lactobacillus paracasei K71 and Lactobacillus sakei probio‐65 in atopic dogs . However, to the best of the authors’ knowledge, no prior report has shown comparable efficacy to a heat‐killed probiotic strain preparation in atopic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal microbiome dysbiosis and the role of microbial modulation in AD development have been of interest . Although the effects of probiotics in the prevention and treatment of AD remain obscure, some reports have shown that oral administration of probiotics, prebiotics or synbiotics can reduce the clinical symptoms or the dosage of medications in human AD, as well as the signs in canine AD (cAD) . Oral administration of lysed Enterococcus faecalis FK‐23 has been mentioned as a potential intervention to reduce allergic responses in mice and humans .…”
Section: Introductionmentioning
confidence: 99%
“…The specific microbial strain could also have influenced our results. Previous veterinary studies were optimistic for improvement of AD with Lactobacillus species intended for humans (Marsella 2009, Inoue et al 2014, Kim et al 2015, Ohshima-Terada Notay et al 2017). Support exists for altered immune parameters in puppies supplemented with SF68 for more than 18 weeks (Benyacoub et al 2003) as well as E. faceium FC-K in laboratory models of Th2-polarised disease (Rho et al 2017), but fewer studies report use of enterococcal species in human and canine adults with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies with Lactobacillus in adult dogs reported promise for a drug-sparing effect (Bermudez-Brito et al 2012, Kim et al 2015, Ohshima-Terada et al 2015. Enterococcus faecium SF68 (FortiFlora; Purina Pro Plan Veterinary Diets) is a hydrolysed commercially-available lactic acid-producing bacterium formulation licensed for veterinary use and has been shown to have immunomodulatory effects in young healthy dogs (Benyacoub et al 2003).…”
Section: Introductionmentioning
confidence: 99%